DEVELOPMENT OF INTERACTIVE MULTIMEDIA BASED MULTIPLE INTELLIGENCE ON THE SOUND WAVES FOR STUDENTS OF CLASS XII SENIOR HIGH SCHOOL - HELSY DINAFITRI; KETANG WIYONO; ABIDIN PASARIBU (Sriwijaya University Learning and Education International Conference, 2016)
This study aims to produce interactive multimedia based multiple intelligence on the sound waves for students of class XII High School are valid, practical and know the potential effects of use. The method used is development research by adapting Rowntree development model which consists of several steps: (1) the planning stage; (2) the development stage; and (3) the evaluation stage. Phase evaluation is done by using Tessmer formative evaluation model consisting of five stages, namely: (1) self evaluation; (2) The expert review; (3) one-to-one evaluation; (4) small group; and (5) field test. Data collection techniques used are sheets of expert validation, questionnaire responses and test student learning outcomes. The results showed on the stage of expert reviews on a percentage of average total validator experts of 93.6% to the category of very valid and at the stage of a small group average percentage of 96.78% with a very practical category. The test results on the field test phase obtained N-gain of 0.69 which showed an increase in the potential effects of the use interactive multimedia based multiple intelligences on the sound waves included in the medium category. Based on the results of this study concluded that interactive multimedia based multiple intelligences on the sound waves for students of class XII High School developed have been valid, practical and have a potential effect on improving student learning outcomes.